2014
DOI: 10.1128/aac.04120-14
|View full text |Cite
|
Sign up to set email alerts
|

Penicillinase-Producing Plasmid Types in Neisseria gonorrhoeae Clinical Isolates from Australia

Abstract: h Penicillinase-producing Neisseria gonorrhoeae (PPNG) carrying the bla TEM-135 gene is of particular concern, as it is considered a stepping stone toward resistance to extended-spectrum cephalosporins. Here, we sought to characterize plasmid types and the occurrence of the bla TEM-135 gene for N. gonorrhoeae clinical isolates from Australia. We found that bla TEM-135 was prevalent in Australian PPNG and was detected on all three major plasmid types. High-level resistance to penicillin in Neisseria gonorrhoeae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
2
8
1
Order By: Relevance
“…This observation corroborates the diversity and emergence of new STs described in previous studies focusing on the epidemiology of PPNG isolates [9,11e15]. Moreover, the STs that we identified were mostly different from those described in Europe [14,15], South America [13], Asia [12], and Australia [9]. Here, we found that 29.5% (52/176) of isolates belonged to four major clusters related to either ST1479 and ST1582 (10.2% and 8.5%, respectively), or to ST8922 and ST1285 (5.6% and 5.1%, respectively) ( Fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This observation corroborates the diversity and emergence of new STs described in previous studies focusing on the epidemiology of PPNG isolates [9,11e15]. Moreover, the STs that we identified were mostly different from those described in Europe [14,15], South America [13], Asia [12], and Australia [9]. Here, we found that 29.5% (52/176) of isolates belonged to four major clusters related to either ST1479 and ST1582 (10.2% and 8.5%, respectively), or to ST8922 and ST1285 (5.6% and 5.1%, respectively) ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found 8% (14/176) of the PPNG isolates to be harbouring the M182T variant of TEM-135 (Table 1), whereas previous studies found higher frequencies of this variant: 10% in Thailand [11], approximately 27% in Argentina, Australia, and the UK, [9,13,14] and 58% in China [12]. In the studies carried out in Thailand and Argentina, TEM-135 was mainly harboured by a Toronto/Rio plasmid [11,13], whereas the studies conducted in Australia and UK found a higher prevalence of African and Asian plasmids [9,14]. Here, we found that the bla TEM-135 gene was embedded in both the Toronto/Rio (6/14, 42.9%) and Asian (8/14, 57.1%) plasmids.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…To date, eight plasmid types have been described in N. gonorrhoeae and named after their epidemiological origin as African, Toronto/Rio, Asian, Nîmes, New Zealand, Johannesburg, and Australian plasmids (5-7). The PPNG isolates carrying a bla TEM-135 gene were found in Thailand, Japan, and China and recently reported in Australia and 15 other countries (8)(9)(10)(11)(12). TEM-135 differs from TEM-1 by a single nucleotide substitution at position 539, resulting in a single amino acid substitution, M182T.…”
mentioning
confidence: 99%